2021
DOI: 10.1097/mbp.0000000000000526
|View full text |Cite
|
Sign up to set email alerts
|

Interarm blood pressure differences and 2-year mortality in acute coronary syndrome patients

Abstract: Background and aims Interarm blood pressure difference (IABPD) was associated with increased cardiovascular and all-cause mortality in various cohorts previously. In this study, we planned to explore the association between the IABPD obtained with simultaneous measurements in both arms and the risk of mortality over a 2-year follow-up of patients with acute coronary syndrome (ACS). Methods Simultaneous blood pressure (BP) measurements were performed dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…The median follow‐up duration ranged from 342 days to 16.4 years. Six studies had a prospective cohort design 16 , 18 , 20 , 21 , 24 , 25 and the remainder were retrospective cohort studies. 9 , 17 , 19 , 26 All the study populations contained a proportion of patients with hypertension or diabetes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The median follow‐up duration ranged from 342 days to 16.4 years. Six studies had a prospective cohort design 16 , 18 , 20 , 21 , 24 , 25 and the remainder were retrospective cohort studies. 9 , 17 , 19 , 26 All the study populations contained a proportion of patients with hypertension or diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…First, there was some moderate heterogeneity in all‐cause comparisons at an IASBPD cutoff of 10 mm Hg. The results of the sensitivity analysis suggested that the study by Kilic and coworkers 20 was the source of this heterogeneity. Their study included patients with ACS and excluded stroke, a history of subclavian artery stenosis, and patients who needed inotropic therapy, all of which can be associated with mortality.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The differences between the present and previous studies should be clarified. Kilic et al investigated the association between the IABPD and all-cause death in 532 patients with acute coronary syndrome (30) and found no significant association between these item at two-year follow-up. The age was younger in their study (mean, 60.1 years old) than in our study (median, 70 years old), but the median follow-up duration was comparable between their study (23.2 months) and our study (694 days [23.1 months]).…”
Section: Discussionmentioning
confidence: 99%